Can digitalization improve the equality and equity of food environment? Evidence from greengrocers in central Shanghai - He, Zhongyu; Chen, Xiaoxu (Frontiers in Nutrition, 2024)
Online food shopping has a profound impact on people's food acquisition behavior, yet little is known how that may affect the accessibility of the local food environment and further influence the health equity among different populations. Taking 8512 traditional and online greengrocers in central Shanghai as an example, this paper uses Gini coefficient, location quotient and spatial clustering method to compare the equality and equity of food environment between physical and digital food outlets. It finds that spatial equality is more significantly improved as a result of online food stores than are population equality and social equity of the food environment; older populations are not disadvantaged in terms of healthy food access but lower-income people are; the impact of online stores varies for different regions and different types of stores; depot-based stores have the most positive impact on health equity. Policy implications are discussed to promote the environmental justice of healthy food accessibility.